k-Simplicity of Leavitt Path Algebras with Coefficients in a k-Semifield - Gupta Raibatak Sen; Sen M.K. (Discussiones Mathematicae - General Algebra and Applications, 2022)
In this paper, we consider Leavitt path algebras having coefficients in a k-semifield. Concentrating on the aspect of k-simplicity, we find a set of necessary and sufficient conditions for the k-simplicity of the Leavitt path algebra LS(Γ) of a directed graph Γ over a non-zeroid k-semifield S.